Levels of Erythrocyte Oxidant and Antioxidant Parameters in People with Alcohol Addiction - Armutcu, Ferah; Gürel, Ahmet; Söğüt, Sadık; Aksu, Neriman; Ünalacak, Murat (Fırat University, 2004)
Aim: Alcohol addiction is one of the leading reasons of liver diseases in many countries. Hepatic steatosis, alcoholic hepatitis, hepatic fibrosis and cirrhosis can be mentioned among the diseases resulting due to alcohol addiction. In recent years, studies have been focused on effect of oxidant stress, in the process of pathological changes and mentioned diseases caused by alcohol. In this study, 25 alcohol addict males were taken as the study group and 25 healthy, non-alcoholic males were taken as control, and oxidant-anti-oxidant status of erythrocytes was evaluated. Materials and Methods: It was measured erythrocyte levels of malondialdehyde, (MDA), which is an indicator of lipid peroxidation, nitric oxide (NO) levels, and activity of xanthine oxidase (XO), which are some of the reasons of oxidant stress, superoxide dismutase (SOD) and catalase (CAT) activities, which are intracellular antioxidant enzymes, were evaluated. Results: While MDA (p:0

Amaç: Alkol alışkanlığı; bir çok ülkede karaciğer hastalıklarının önde gelen nedenleri arasındadır. Aşırı alkol tüketimi veya alkol alışkanlığı sonucunda meydana gelen karaciğer patolojileri arasında hepatik steatozis, alkolik hepatit, hepatik fibrozis ve siroz yer almaktadır. Son yıllarda alkolün yol açtığı patolojik değişikliklerin ve bu hastalıkların oluşum sürecinde oksidan stresin etkisi üzerinde durulmaktadır. Bu çalışmada alkol alışkanlığı olan 25 erkek deney grubu ile alkol almayan 25 sağlıklı erkek kontrol grubu eritrositlerinin oksidan ve antioksidan durumu değerlendirilmiştir. Gereç ve Yöntem: Lipid peroksidasyonunun göstergesi olan malondialdehid (MDA) düzeyleri, oksidan stres nedenlerinden olan nitrik oksit (NO) düzeyi ve ksantin oksidaz (XO) aktivitesi, hücre içi antioksidan enzimlerden süperoksit dismutaz (SOD) ve katalaz (CAT) aktiviteleri değerlendirildi. Bulgular: Alkol alışkanlığı olanlarda eritrosit MDA (p0.05) düzeyleri kontrol grubundan yüksek bulundu. Alkol kullananlarda eritrosit SOD (p
Alkol Alışkanlığı Olanlarda Eritrosit Oksidan ve Antioksidan Parametre Düzeyleri